2021
DOI: 10.3390/cancers13092277
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Factors in Melanoma Pathogenesis

Abstract: Melanoma is one of the most aggressive skin cancers with a sharp rise in incidence in the last decades, especially in young people. Recognized as a significant public health issue, melanoma is studied with increasing interest as new discoveries in molecular signaling and receptor modulation unlock innovative treatment options. Stress exposure is recognized as an important component in the immune-inflammatory interplay that can alter the progression of melanoma by regulating the release of neuroendocrine factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 336 publications
0
17
0
Order By: Relevance
“…A high level of vitamin D is associated with a low tumoral thickness and protects against relapses and death caused by melanoma [ 45 , 61 ]. Some studies suggest that neuroendocrine factors may play a role in melanoma development, influencing the tumoral cells’ proliferation and metastasis capability [ 62 ]. For example, catecholamines stimulate proliferation, motility, and invasion of melanoma cells, while glutamate may activate angiogenesis [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…A high level of vitamin D is associated with a low tumoral thickness and protects against relapses and death caused by melanoma [ 45 , 61 ]. Some studies suggest that neuroendocrine factors may play a role in melanoma development, influencing the tumoral cells’ proliferation and metastasis capability [ 62 ]. For example, catecholamines stimulate proliferation, motility, and invasion of melanoma cells, while glutamate may activate angiogenesis [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it can be obviously assumed that, along with the studied components of the secretome, specific proteases, which entered the extracellular matrix, also exerted their effects. It is also necessary to consider the components of the secretome with neuroendocrine effects, namely, histamine, VEGF, IL-8, heparin, and TGF-β [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combining this with the study that found TSH can promote the growth of melanoma by triggering the formation of cAMP and activating the mitogen-activated protein kinase (MAPK) signaling pathway, may in part account for the high prevalence of hypothyroidism (elevated TSH lever) in the melanoma population [48,49]. Intriguingly, another study has reported that suppression of MAP kinase and PI3KAkt pathways exhibits their anti-melanoma effects, including suppression of cell proliferation, transformation, and invasion, and these effects are coupled with inducing the expression of thyroid genes, such as TSH-R and NIS, and consequently increasing radioiodide uptake by melanoma cells, which may prove to be a novel approach to treating melanoma [50,51].…”
Section: Hypothalamic-pituitary-thyroid Axis (Hpt) Homologmentioning
confidence: 99%